The Effect of Crossword Puzzle Learning Strategies on Fourth Grade Students' Learning Outcomes on Science Learning Contents at Gunung Sari 1 Elementary School Rappocini District Makassar City - Arindah Pratiwi (Program Studi PGSD FIP UNM, 2021)
ABSTRACTThis research is a pre-experimental research which aims to determine whether or not there is an effect of the crossword puzzle learning strategy on the learning outcomes of fourth grade students on science learning content at Gunung Sari 1 elementary school, Rappocini District, Makassar City. The independent variable in this study is the crossword puzzle learning strategy, while the dependent variable is the student learning outcomes in science learning content. The population and sample in this study were fourth grade students of Gunung Sari 1 elementary school, Rappocini District, Makassar City, with a total of 26 students. The research data obtained by giving a test of learning outcomes on the theme of caring for living things, sub-themes of animals and plants in my home environment in the form of pretest and posttest. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. Based on the results of the descriptive statistical analysis that has been carried out, it can be concluded that the pretest score is in this good category because the mean value of overall learning outcomes is 80.19 while from the posttest it is also in the good category because based on the overall mean value of learning outcomes is 83.27 while The results of inferential statistical analysis after the normality test using the Kolmogorov-Smirnov test with pretest and posttest data are normally distributed and the results of hypothesis testing using the paired sample T-test whose probability value is 0.000 <0.05, which means that Ho is accepted and Ha is rejected because the test criteria are if the probability value greater than the significance level of 0.05, Ho is accepted and Ha is rejected, in other words, the pretest and posttest data have a significant difference. It can be concluded that the crossword puzzle learning strategy has a significant effect on the fourth grade learning outcomes of science learning content at SDN Gunung Sari 1 Rappocini District Makassar City. Keywords: learning strategies, crossword puzzle, learning outcomes